Multiple roles for membrane-associated protein trafficking and signaling in gravitropism - Strohm, Allison K.; Baldwin, Katherine L.; Masson, Patrick H. (Frontiers in Plant Science, 2012)
Gravitropism is a process that allows plant organs to guide their growth relative to the gravity vector. It requires plant organs to sense changes in their orientation relative to the gravity vector and then generate a biochemical signal that they transmit to a responding zone where a curvature response will ensue, realigning the organs’ growth relative to gravity. Trafficking between the plasma membrane and endosomal compartments is important for all of these phases of the gravitropic response. The sedimentation of starch-filled organelles called amyloplasts plays a key role in sensing reorientation, and vacuolar integrity is required for amyloplast sedimentation in shoots. Other proteins associated with the vesicle trafficking pathway contribute to early gravity signal transduction independently of amyloplast sedimentation in both roots and hypocotyls. Phosphatidylinositol signaling, which starts at the plasma membrane and later affects the localization of auxin efflux facilitators, is a likely second messenger in the signal transduction phase of gravitropism. Finally, membrane-localized auxin influx and efflux facilitators contribute to a differential auxin gradient across the gravistimulated organs, which directs root curvature.